Seismic design for reinforced concrete office building influenced by concrete grade and level of seismicity - Azlina, Nordin (2019)
Earthquake is a natural disaster that may lead to collapsing of building. Office building is a place the employee do their work, when earthquake happened, the building will not be able to withstand the earthquake which may be dangerous to people. So, in order to be a safe place, the building must withstand the disaster such as earthquake. Malaysia is considered to have a low seismicity profile but more evidences are showing that early assumption Malaysia is free from earthquake are misleading. The earthquake on 2004 Indian-Ocean earthquake with magnitude 9.1 which killed 68 lives in Malaysia and thousands others in Indonesia, Sri Lanka and Thailand. Therefore, this work will focus on study the effect of seismic design on the weight of steel reinforcement and volume of concrete used for office building. The first objectives is to study the effect on magnitude of PGA on the amount of steel reinforcement. The second objectives is to study the effect on grade of concrete on the amount of steel reinforcement. And the third objectives for this research is to study the influence of PGA and grade of concrete on cost estimation. In the total of 16 models of reinforced concrete office building with number of 3 and 6 storeys will be used in this analysis. The models will be design for two different grade of concrete which are G25 and G30. The value of PGA will be fixed as 0.03g, 0.09g and 0.15g. This study only considered the ductility class medium and soil type D. Tekla structure software will be used for analysis and designed based on Eurocode 8 (2004). The comparison will be made in term of amount of steel required as 1m3 of concrete for every model. For different magnitude of PGA, the result shows that the percentage difference of steel reinforcement required to non-seismic model of 3-storey and 6-storey office building had increased from 2%, 14% and 56% and 7%, 49% and 162% for reference peak ground acceleration, agR = 0.03g, 0.09g and 0.15g respectively. While for different value of grade of concrete, the result shows that the percentage difference of steel reinforcement required to non-seismic model of 3-storey and 6-storey office building had decrease from 36% to 56% and 162% to 139% respectively according to different grade of concrete. Thus, magnitude of PGA and concrete grade of structure give significant effect to overall amount of steel reinforcement required. Hence, it should be considered in designing a seismic building.